Perceived effects of teaching caregivers on the activities of daily living performance of post-stroke patients - Famorca, Mary Josephine M. (1998)
This study aimed to determine the perceived effects of teaching caregivers on the activities of daily living performance of post-stroke patient. The objectives of this study were:1. To determine if an increased competence of caregivers after a Teaching Program has an effect on the activities of daily living performance of post-stroke patients.2. To determine if there is any difference in caregiver competence (knowledge, skill and attitude) before and after the teachiong program.3. To determine the perceived effects of teaching caregivers on the activities of daily living performance of post-stroke patients.A one group pre-test-post test design was used in the study. The following instruments were used for data collection: Caregiver Profile form and Patient Profile form; Test about stroke, Skill Performance Checklist, Attitude Score for caregivers; Index Score for patients ADL. Sample subjects were generally taken from the patients of UERMMM Hospital. There were ten (10) patients and ten (10) caregivers who qualified for the study. Pre-testing and post-testing of caregivers knowledge, skill and attitude were done in the hospital. Post-test of patients activities of daily living skill was done three (3) weeks after patient were discharged, at their place of residence.The data were analyzed using tabular analysis. The difference between the sample means for both patients and caregivers was determined.The findings of the study are:1. There were an equal distribution of patients male and female (n=10), with the mean age of 45 years old, generally married and with college of education. Most of the patients had thrombosis as a cause of stroke with left sided weakness.2. There were more female caregivers with the mean age of 26 years old, single, with high school education, related and living with the patients.3. There was an observed increased in caregiver competence in terms of skill, knowledge, attitude after the teaching program. Scores were observed higher on the skill component.4. There was an improvement in activities of daily living scores after the caregiver teaching program.5. The following caregiver characteristics (sex, education, civil status and relationship to patient) were observed to influence caregiver competence.6. Patient characteristics (age, sex, education and type of stroke disability) were observed to influence activities of daily living performance. Those with left sided weakness were able to perform better in terms of activities of daily living.7. The pre-test and post-test scores of patients activities of daily living was significant beyong the p=0.0005 level at 9 degress of freedom with t value of 5.53. This result can only be attributed to this sample.
8 Observation made by the investigator for the ten caregiver-patient dyad showed that patients who were aware of their need to improve oneself; who were given an opportunity to care for themselves and who were appropriately praised improved their ADL scores after the teaching program.9. Interview with caregivers revealed that there were conscious effort on their part of utilize the teachings given to them like passive range of motion exercise, proper giving of praise and allowing patient to do self-care tasks. One major reason why they persevere in caring for the patient were feelings of obligation, reciprocity and love. The latter reason mostly exhibited by caregivers who were related to the patient. Other relatives were also recruited and taught by primary caregivers regarding the care of their patient. Majority of the family of the post-stroke patients experienced role disruption which they tried to cope in various ways.From the findings of the study, the following implications are made. The findings reinforced the advocate role of nurses in providing a teaching program to help post-stroke patients in their rehabilitation. Furthermore, the active participation of patient's primary caregiver produced favorable outcome on patients rehabilitation. Results of this study indicate that a Teaching Program for caregivers can be recommended for nurses for stroke patients before they are discharged in order to enhance their capability to perform their activities of daily living.
Thesis (Master of Arts in Nursing)--University of the Philippines Manila.
Keywords: Caregivers; Post-stroke patients